Prevalence of diarrhea and water sanitation and hygiene (WASH) associated factors among children under five years in Lira City Northern Uganda: Community based study - Auma, Brenda; Musinguzi, Marvin; Ojuka, Edward; Kigongo, Eustes; Tumwesigye, Raymond; Acup, Walter; Kabunga, Amir; Opio, Bosco (Public Library of Science, 2024)
Background Children under the age of five experience a significant disease burden from diarrheal illnesses. This poses a severe public health risk as the second leading cause of infant death worldwide, after pneumonia. Lira City in Uganda is one of the developing urban areas with limited information about the diarrheal disease among children under the age of 5 years. This study aimed to determine the prevalence and assess the water, sanitation and hygiene related factors associated with diarrheal diseases among children under five years in Lira City. Methods The study was conducted among 492 care takers of children under the age of 5 years in Lira City between August 2022 and September 2022. Data was collected using an interviewer administered questionnaire and a multi-stage sampling was used to select study participants. Data was analyzed by bivariate and multivariate logistic regression using STATA version 17. P-value of < 0.05 was considered statistically significant. Results Out of 541 participants, 492 responded. The majority of the respondents, 425(86.4%) were female, 146(29.7%) had children aged 1–12 months, 192 (39%) had primary level education, and 155(31.5%) were self-employed. The prevalence of diarrhea among children under five years was 130(26.4%) and the associated factors with diarrheal disease were children between 49–60 months old (AOR = 0.12, 95% CI : 0.03–0.39, P = 0.001), cleaning the latrine more times (AOR = 0.42, 95% CI : 0.22–0.81, P = 0.010) and not treating water (AOR = 1.84, 95% CI : 1.11–3.06, P = 0.018). Conclusion There is high prevalence of diarrhea among children under 5 years of age. The study’s findings highlight the need for ongoing efforts to lower the prevalence of diarrheal illnesses among children under the age of five in Uganda’s emerging urban areas.